Sustainable Development in Mountain Regions Southeastern Europe - Zhelezov, Georgi (Springer International Publishing : Imprint: Springer, 2016)
This second edition of the book Sustainable Development of Mountain Regions: Southeastern Europe integrates the scientific results and expertise of the researchers from the countries in Southeastern Europe. The book consists of updated information for the topics observed in first edition and several new chapters with analysis of some problems in the mountain regions of four new for the edition countries in Southeastern European space. The general themes in the book are related to Global problems and mountain regions; Nature resources and landuse in mountain regions; Social, economic and regional problems of mountain regions; Nature protection, conservation and monitoring and Networks and strategies for mountain regions. The key topics for discussion are: Natural recourses and land use in mountain regions. Sustainable social and economic development of the mountain regions. Natural disasters and risk prevention. Spatial modeling and planning. Nature protection, monitoring and conservation. Politics and sustainable practices for development of mountain regions. Transborder and regional cooperation. Mountain regions in Southeastern Europe are characterized by unique landscape and biological diversity and great economic potential. They have function as a living space and provide different groups of ecosystem and landscape services. In social and economic aspects these regions are one of the poorest in Southeastern European countries with unused potential. Human, ecological and economic problems arising in various mountain regions have the same basic characteristics irrespective of the country. Some mountain regions are subject to specific for the conditions of the mountain and country policy for planning, development and mountain population promotion. The general goal is development of whole economy and the efficient management of natural resources and prevention of natural and technological disasters. The mountain regions are one of the most threatened landscape systems in Southeastern Europe. Understanding the importance of the mountain regions and conservation of the natural heritage require scientific and institutional cooperation at all levels.